Multiple bile duct adenomas mimicking hepatic metastases during laparoscopic cholecystectomy - A case report - Subasinghe, Duminda; Mithushan, Jesuthasan; Abeysinghe, Anjana; Withanage, Rachini; Ranaweera, G.G. (Elsevier, 2025)
Introduction and importance: Bile duct adenoma (BDA) is a rare benign liver neoplasm, with relatively few cases reported in literature. Case presentation: A 55-year-old man diagnosed with symptomatic gallstone disease who underwent elective laparoscopic cholecystectomy. During the procedure, there were multiple liver nodules mimicking hepatic metastases. Histological examination and contrast-enhanced computed tomography (CECT) of the liver confirmed the diagnosis of BDA. Discussion: When incidental liver nodules are encountered intraoperatively, thorough evaluation is essential to confirm the diagnosis. Structured approach using histological examination and imaging (CECT of the liver/ MRI) confirmed the diagnosis of BDA. Conclusions: BDA is a rare benign liver neoplasm that can be challenging to differentiate from hepatocellular carcinoma or liver metastases. Accurate identification of BDA can prevent overtreatment or mismanagement.
Keywords: Bile duct adenomas; Hepatic metastases; Laparoscopic cholecystectomy